Penerapan Biaya Standar Dalam Pengendalian Biaya Produksi - Dewi Anggraini; Yuli Nurhayati (COSTING : Journal of Economic, Business and Accounting, 2020)
This study aims to determine the control of production costs by applying standard costs in the Kerupuk Khas Malalo Industry of Lubuklinggau City. This research is a qualitative research. The data sources used are primary data sources and secondary data sources. The data collection techniques used were interviews, observation and documentation. The results showed that the Jangek Khas Malalo Crackers Industry in Lubuklinggau City experienced an unfavorable difference in purchasing raw materials, controlling labor costs had not been effective because of the increase in wage rates and the addition of one employee as well as controlling factory overhead costs as well. has not been effective because it does not perform calculations in accordance with the actual calculation. In conclusion, the Jangek Khas Malalo cracker industry in Lubuklinggau City has not controlled production costs properly in production activities and has experienced an unfavorable difference due to the increase in costs incurred in production activities. Keywords: Production Costs, Standard Costs, Control